The relationship between counterproductive work behavior and emotional intelligence among pest control employees - Evi Susanti; Adam Ahmad Alwansyah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
The primary purpose of this research is to study the effect of emotional intelligence (EI) on the counterproductive work behavior (CWB) of employees in the pest control industry in Indonesia. Although the effect of EI on CWB can be analyzed using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT), this model is not specific to employees; for this reason, EI will be measured via the Wong and Law Emotional Intelligence Scale (WLEIS). Questionnaires were distributed to 585 pest control employees. The data were analyzed using structural equation modeling (SEM). The results indicate that EI has a statistically significant negative relationship with CWB and that the more emotionally intelligent employees are, the less likely they will be to act counterproductively at work. These findings can potentially reduce the level of CWB for organizations and society by enabling companies to assess the EI of workers.